Struktur dan Fungsi Pantun dalam Teks Cerita Santan Batapih dalam Seni Pertunjukan Tradisional Basijobang di Kabupaten Lima Puluh Kota - Maharani, Addiena Intan; Zulfadhli (Universitas Negeri Padang, 2024)
The purpose of this research is to identify the structure and function of pantun in the Santan Batapih story text in the traditional Basijobang performing arts in Limapuluh Kota Regency. This research is literary research that uses descriptive methods. Data collection uses interview techniques supported by note-taking and recording, as well as through field observation methods. The data source in this research is the pantun in the story text Santan Batapih in the traditional Basijobang performing arts in Limapuluh Kota Regency. The data in the research was analyzed using four stages, namely: (1) transcribing the data, (2) classifying, (3) analyzing and interpreting the data, and (4) concluding the results of the research and writing research results reports. The results obtained from this research are: (1) the structure of the pantun in the text of the Santan Batapih story in the Basijobang Performance consists of stanzas, lines, rhymes, endings, and content. (2) the function of pantun in the story text of Santan Batapih in the Basijobang Performance which consists of opening the story, changing the story, content of the story, aesthetics and closing the story.